Working on the weekend: Do analysts strategically time the release of their recommendation revisions? - Rees, Lynn; Sharp, Nathan Y.; Wong, Paul A. (Journal of Corporate Finance, 2017)
We examine whether financial analysts strategically time the announcement of their recommendation revisions consistent with their incentives to maintain relations with management. We provide evidence that investor and media attention to recommendation revisions is reduced on weekends, which analysts can exploit to strategically time the release of their revisions. We find that downgrades are a higher proportion of weekend revisions than weekday revisions and that analysts with characteristics that suggest they possess the strongest incentives to maintain favor with management are more likely to downgrade on the weekend. In contrast, analysts absent these characteristics are more likely to release downgrades during the week, consistent with these analysts being driven primarily by other incentives, such as the timely release of their recommendation and garnering media attention. We also present evidence suggesting that strategic disclosure of recommendation downgrades is associated with greater access to management on public earnings conference calls.